Pengembangan Pemasaran Produk Ikan Patin Berkualitas Berbasis Pasar Online di Rumbai Bukit Pekanbaru - Mainil, Rahmat Iman; Hasibuan, Saberina; Syawal, Henni; Darfia, Novreta Ersyi; Martina, Atria (Unri Conference Series: Community Engagement, 2024)
The Mina Usaha Fish Cultivation Group (Pokdakan) is located in the Rumbai Bukit area, Rumbai District, Pekanbaru, Riau with patin fish as the main aquaculture commodity. Community service activities that overcome the problem of cultivated fish often experiencing mass mortality have been carried out in the first year by increasing knowledge about aspects of aquaculture activities. The problems faced by cultivators in terms of providing quality feed and pond sedimentation rate have also been carried out in the second year. In this third year, processing and marketing activities for various quality patin fish products based on the online market are carried out. The harvest from the Mina Usaha Pokdakan cultivation pond has not been processed optimally into processed products due to the limited knowledge and skills of cultivators in product processing. Assistance and coaching in the processing of harvested products and the development of marketing of various quality patin fish products based on the online market are the main focus of service activities. The activities carried out are preparation for implementation, surveys and market analysis to identify superior patin fish products, discussions and consultations to design product development strategies in tandem with online platform development activities, delivery of materials to empower cultivators in the aspects of maintenance, processing, and improvement of product quality and materials on the use of online platforms, and the implementation of diversified products is carried out through product procurement, promotions, and online advertising. The products that were successfully made were nuggets, fish balls, and surimi. This frozen food product has also been successfully sold through the online market. Implementation evaluations are carried out on an ongoing basis to ensure the effectiveness of activities and allow for adjustments if necessary. The results of the evaluation showed that the enthusiasm of the participants who participated in the activity was very high.